Air Convection in the Active Layer of Rock Glaciers - Wicky, Jonas; Hauck, Christian (Frontiers in Earth Science, 2020)
Coarse blocks are an abundant surface cover in mountainous permafrost landscapes. In this coarse blocky layer, air convection occurs and has a significant influence on the ground thermal regime of the underlying permafrost. Besides heat transfer through conduction, free convection of air takes place seasonally and leads to a pronounced ground cooling. Air convection has been observed and described in many field studies but is often neglected or parametrized in permafrost modeling. In the present study, air convection in the active layer of rock glaciers is explicitly modeled through a heat conduction equation coupled with Darcy’s law over a two-dimensional geometry. With a series of numerical experiments, we show its effects on the thermal regime of the underlying permafrost. The ground permeability and the thermal gradient in the active layer are the most important parameters for air convection in the ground. On field sites with a high ground permeability (order of magnitude 10 6 m2), convection plays a crucial role and is required to correctly model measured borehole temperatures. The onset of natural convection occurs at critical Rayleigh numbers and is characterized by an increase of the standard deviation of the direction and the vorticity of the airflow field in the active layer. In the numerical solutions, the internal air circulation in the coarse blocky surface layer leads to an efficient ground cooling.